2015
DOI: 10.1016/j.neuropsychologia.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of meaning: Behavioral and neuroanatomical dissociation of semantically-driven word retrieval and multimodal semantic recognition in aphasia

Abstract: Theories about the architecture of language processing differ with regard to whether verbal and nonverbal comprehension share a functional and neural substrate and how meaning extraction in comprehension relates to the ability to use meaning to drive verbal production. We (re-)evaluate data from 17 cognitive-linguistic performance measures of 99 participants with chronic aphasia using factor analysis to establish functional components and support vector regression-based lesion-symptom mapping to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 64 publications
9
114
0
Order By: Relevance
“…Previous studies using different task paradigms have implicated damage to the left IFG, pSTG/pMTG, and pSMG/AG, in deficits of auditory comprehension and/or discrimination (Bates et al, 2003, Dronkers et al, 2004, Fridriksson et al, 2013, Geva et al, 2012, Pustina et al, 2016, Yourganov et al, 2016), and have implicated anterior temporal lobe lesions in semantic deficits when controlling for deficits in comprehension (Mirman et al, 2015a, Mirman et al, 2015b, Schwartz et al, 2009, Walker et al, 2011). Importantly, all of these regions were identified by our analysis, and are associated with the semantic network recruited by this task (Binder et al, 1997, Binder et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using different task paradigms have implicated damage to the left IFG, pSTG/pMTG, and pSMG/AG, in deficits of auditory comprehension and/or discrimination (Bates et al, 2003, Dronkers et al, 2004, Fridriksson et al, 2013, Geva et al, 2012, Pustina et al, 2016, Yourganov et al, 2016), and have implicated anterior temporal lobe lesions in semantic deficits when controlling for deficits in comprehension (Mirman et al, 2015a, Mirman et al, 2015b, Schwartz et al, 2009, Walker et al, 2011). Importantly, all of these regions were identified by our analysis, and are associated with the semantic network recruited by this task (Binder et al, 1997, Binder et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear that this functional connectivity should implicate a single white matter tract such as the SLF or arcuate fasciculus. A recent study of 99 participants with aphasia following left hemisphere stroke found that deficits in recognizing semantic relationships were associated with damage to a frontal “white matter bottleneck” that affected the inferior fronto-occipital fasciculus, the uncinated fasciculus, and the anterior thalamic radiations (Mirman et al, 2015a; 2015b). Mirman et al interpreted this result to mean that semantic cognition requires widespread connectivity between frontal regions and other brain regions involved in semantic memory, rather than a single connection between any two regions.…”
Section: Discussionmentioning
confidence: 99%
“…citations). Although it has become common practice to explain results of neuroimaging studies of speech processing in the context of dual stream models (16)(17)(18)(19)(20)(21), the specific location and extent of the dorsal and ventral streams involved in speech processing, each of which is a theoretical construct based on either animal data (5) or the combination of lesion and functional neuroimaging data in humans (8), remain elusive.…”
Section: Significancementioning
confidence: 99%
“…Other studies have used a principal components analysis (PCA) step as part of the analysis relating localized brain damage to behavioral impairment (19,31,32). However, those studies differed from this approach in that each carried out PCA on the behavioral data and then, included the components as dependent factors in a voxel-based lesion-symptom mapping (VLSM) analysis.…”
Section: Significancementioning
confidence: 99%